Management of Patients With Pancreatic Cysts: Analysis of Possible False-Negative Cases of Malignancy. Issue 8 (September 2016) - Kowalski, Thomas; Siddiqui, Ali; Loren, David; Mertz, Howard R.; Mallat, Damien; Haddad, Nadim; Malhotra, Nidhi; Sadowski, Brett; Lybik, Mark J.; Patel, Sandeep N.; Okoh, Emuejevoke; Rosenkranz, Laura; et al.
Abstract : Goals: To examine the utility of integrated molecular pathology (IMP) in managing surveillance of pancreatic cysts based on outcomes and analysis of false negatives (FNs) from a previously published cohort (n=492). Background: In endoscopic ultrasound with fine-needle aspiration (EUS-FNA) of cyst fluid lacking malignant cytology, IMP demonstrated better risk stratification for malignancy at approximately 3 years' follow-up than International Consensus Guideline (Fukuoka) 2012 management recommendations in such cases. Study: Patient outcomes and clinical features of Fukuoka and IMP FN cases were reviewed. Practical guidance for appropriate surveillance intervals and surgery decisions using IMP were derived from follow-up data, considering EUS-FNA sampling limitations and high-risk clinical circumstances observed. Surveillance intervals for patients based on IMP predictive value were compared with those of Fukuoka. Results: Outcomes at follow-up for IMP low-risk diagnoses supported surveillance every 2 to 3 years, independent of cyst size, when EUS-FNA sampling limitations or high-risk clinical circumstances were absent. In 10 of 11 patients with FN IMP diagnoses (2% of cohort), EUS-FNA sampling limitations existed; Fukuoka identified high risk in 9 of 11 cases. In 4 of 6 FN cases by Fukuoka (1% of cohort), IMP identified high risk. Overall, 55% of cases had possible sampling limitations and 37% had high-risk clinical circumstances. Outcomes support more cautious management in such cases when using IMP. Conclusions: Adjunct use of IMP can provide evidence for relaxed surveillance of patients with benign cysts that meet Fukuoka criteria for closer observation or surgery. Although infrequent, FN results with IMP can be associated with EUS-FNA sampling limitations or high-risk clinical circumstances. Abstract : Supplemental Digital Content is available in the text.